Changes of Soil Chemical Properties during Rice Straw Decomposition in Different Types of Acid Sulphate Soils - Hairani, Anna; Susilawati, Ani (JOURNAL OF TROPICAL SOILS, 2013)
Organic residues often exhibit different physico-chemical properties and affect the soil ecosystem in different ways. Hence, the study of their impact on soil is essential to benefit from their potential as amendments and to avoid adverse environmental effects. It is required to study the role of rice straw in the changes of soil properties during decomposition processes in the rice field. The research was conducted on potential acid sulphate soil (PASS) and actual acid sulphate soil (AASS) in the glass house. Soil pH, Fe2+, organic-Fe, total N and available P were observed at 2, 4, 6 and 8 weeks after planting (WAP). The result showed that rice straw application : (1) decreased soil pH of PASS and increase soil pH of AASS; (2) tended to increase Fe2+ both in PASS and AASS; (3) stimulated the organic-Fe concentration in AASS was higher than organic-Fe concentration in PASS; (4) had no different effect in total N and decreased P concentration in the both of soil during observation. P concentration on PASS was lower than on AASS.Keywords: Decomposition, rice straw, soil chemical properties, soil type[How to Cite: Hairani A and A Susilawati. 2013.Changes of Soil Chemical Properties during Rice Straw Decomposition in Different Types of Acid Sulphate Soils. J Trop Soils 18 (2): 99-103. Doi: 10.5400/jts.2013.18.2.99]REFERENCESBalai Penelitian Tanah. 2005. Analisis Kimia Tanah, Tanaman, Air dan Pupuk.  Badan Penelitian dan Pengembangan Pertanian. Departemen Pertanian.  Bogor. p: 136 (in Indonesian).Banach AM, K Banach, RCJH Peters,  RHM Jansen, EJW Visser, Z Stepniewska, JGM Roelofs and LPM Lamers.  2009.  Effects of long-term flooding on biogeochemistry and vegetation development in floodplains; a mesocosm experiment to study interacting effects of land use and water quality.  Biogeosciences  6: 1325-1339. doi:10.5194/bg-6-1325-2009.Bonneville S.  2005.  Kinetics of Microbial Fe (III) Oxyhydroxide Reduction : The Role of Mineral Properties.  [Dissertation].  Department of Earth Sciences-Geochemistry, Faculty of Geosciences, Utrecht University. The Netherlands. 117 p.Cayuela ML, T Sinicco and C Mondini.  2009.  Mineralization dynamics and biochemical properties during initial decomposition of plant and animal residues in soil. App Soil Ecol  41: 118 -127.De-Campos AB, AL Mamedov and C Huang. 2009. Short-term reducing conditions decrease soil aggregation. Soil Sci Soc Am J  73: 550-559.Dent D. 1986. Acid Sulphate Soils: A Baseline for Research and Development. International Land Reclamation Institute Pub. 39. Wageningen, The Netherlands. 204 p.Dobermann A and T Fairhurst.  2000.  Rice: Nutrient Disorders and Nutrient Management.  International Rice Research Institute.  Makati city, The Fhillipines.  191 p. Fahmi A, B Radjagukguk and BH Purwanto.  2009.  Kelarutan posfat dan ferro pada tanah sulfat masam yang diberi bahan organik jerami padi.  J Tanah Trop 14: 119 -125 (in Indonesian).Fahmi A. 2010.  Pengaruh pemberian jerami padi terhadap pertumbuhan tanaman padi (Oryza sativa ) di tanah sulfat masam.  J Berita Biol 10:  7-14 (in Indonesian). Havlin JL, JD Beaton, SL Tisdale and WL Nelson. 2005. Soil Fertility and Fertilizers, an introduction to nutrient management. 7th edition. Prentice Hall. 515 p.Indrayati L and A  Jumberi. 2002.  Pengelolaan jerami padi pada pertanaman padi di lahan pasang surut sulfat masam.  In: Pengelolaan Tanaman Pangan Lahan Rawa.  Badan Penelitian dan Pengembangan Pertanian, Puslitbang Tanaman Pangan, Bogor. Kirk G.  2004.  The Biogeochemistry of Submerged Soils. John Willey and Sons. Chicester, England.  291 p.Kongchum M.  2005.  Effect of  Plant Residue and Water Management Practices on Soil Redox Chemistry, Methane Emission and Rice Productivity.   [Dissertation].  Graduate Faculty of the Louisiana State University.  USA.  201 pKyuma K.  2004.  Paddy Soil Science.  Kyoto University Press dan Trans Pacific Press.  Melbourne.  Australia. 279 p.Liang X, J Liu, Y Chen, H Li, Y Ye, Z Nie, M Su and Z Xu.  2010.  Effect of pH on the release of soil colloidal phosphorus.  J Soils Sediments 10: 1548-1556.Lindsay WL. 1979.  Chemical Equilibria in Soils. John Willey & Sons. New York. 449 p.Liu C, M Chen and F Li. 2010. Fe(III) reduction in soils from South China. In: RJ Gilkes and N Prakongkep (eds). Soil Solutions for a Changing World. Soil minerals and contaminants, 19th World Congress of Soil Science. Brisbane, Australia, pp.70-73.McIntyre RES, MA Adams, DJ Ford and PF Grierson.  2009.  Rewetting and litter addition influence mineralization and microbial communities in soils from a semi-arid intermittent stream.  Soil Biol Biochem 41: 92-101.Morris AJ. 2011. Phosphate Binding to Fe and Al in Organic Matter as Affected by Redox Potential and pH. [Dissertation]. Soil Science, North Carolina  State University, Raleigh, North Carolina, USA. 229 p.Olomu MO, GJ Racz and CM Cho.  1973.  Effect of flooding on the Eh, pH, and concentrations of Fe and Mn in several manitoba soils.  Soil Sci Soc Am J  37: 220 -224.Ponnamperuma FN. 1984.  Effects of flooding on soils.  In: T Kozlawski (ed).  Flooding and Plant Growth: Physical Ecology. A Series Monographs, Text and Treatises.  Academic Press Inc.  Harcourt Brace Javanovich Publisher, USA, pp. 10-45. Reddy KR and RD Delaune.  2008. The Biogeochemistry of Wetland; Science and Application. CRC Press.  New York.Rukhsana F, C Butterly, J Baldock and C Tang.  2010. Model carbon compounds differ in their effects on pH change of soils with different initial pH. In: RJ Gilkes and N Prakongkep (eds). 19th World Congress of Soil Science, Soil Solutions for a Changing World, 1 – 6 August 2010, Brisbane, Australia,  pp. 160-163.Syahrawat KL.  2006.  Organic matter and mineralizable nitrogen relationships in wetland rice soils.  Commun Soil Sci Plant Anal 37: 787-796. Wagai R and LM Mayer.  2007.  Sorptive stabilization of organik matter in soils by hydrous iron oxides.  Geochim Cosmochim Act 71: 25-35.Watanabe I.  1984.  Anaerobic decomposition of organic matter in flooded rice soils. In: Organic Matter and Rice. Intenational Rice Research Institute.  Los Banos Laguna, Philippines,  pp. 237-258.Wickham TH and VP Singh. 1978.  Water movement through wet soils. Soil and Rice.  International Rice Research Institute. Los Baños, Philippines, pp. 337- 358.